The Implementation of Spiritual Education through Boarding Education Program at State High School in South Sumatera - Muhamad Takrip (Edudeena: Journal of Islamic Religious Education)
Abstract: Spiritual education plays a central role in the holistic development of learners. The focus isn't solely on the intellectual aspect but also encompasses moral development, spiritual values, and wisdom in daily life. This research aims to comprehend the implementation of spiritual education for students through the Boarding Education program at State High School (SMAN) in South Sumatera. It falls under qualitative research, utilizing a case study approach. Data collection methods involve observation, interviews, and documentation. Data analysis techniques employ qualitative data analysis in three stages: data reduction, data display, and conclusion drawing. The research findings indicate that the Boarding Education program in South Sumatera’s SMAN follows the concept of nine house systems: dolphin, dove, eagle, hornbill, Komodo dragon, lion, manta ray, rhinoceros, and shark. Each house is overseen by 4-5 house coordinators. There are three activities within this spiritual program: Quran recitation, Quran memorization, and Islamic discussions. Several Islamic practices are instilled to support the success of this program, such as congregational prayers, a seven-minute lecture after Maghrib prayers, and nurturing character traits within the students.